Interictal Heart Rate Variability Analysis Reveals Lateralization of Cardiac Autonomic Control in Temporal Lobe Epilepsy - Dono, Fedele; Evangelista, Giacomo; Frazzini, Valerio; Vollono, Catello; Carrarini, Claudia; Russo, Mirella; Ferrante, Camilla; Di Stefano, Vincenzo; Marchionno, Luciano P.; De Angelis, Maria V.; Faustino, Massimiliano; Bonanni, Laura; et al. (Frontiers in Neurology, 2020)
Purpose: The temporal lobe, a critical hub for cognition, also plays a central role in the regulation of autonomic cardiovascular functions. Lesions in this area are usually associated with abnormalities in the regulation of heart rate (HR) and blood pressure (BP). The spectral analysis of the heart rate variability (HRV) is useful to evaluate the impairment of the autonomic control of cardiovascular functions. This study aims at comparing HRV changes occurring in two groups of patients suffering from Temporal Lobe Epilepsy (TLE). To that aim, we evaluated patients differentiated by the right or left location of the epileptic foci. Materials and Methods: Fifty-two adult patients with a diagnosis of TLE were enrolled. Each patient underwent a 20-minute EEG + EKG recording in resting state. According to the localization of epileptic focus, patients were divided into two subgroups: right TLE (R-TLE) and left TLE (L-TLE). HRV parameters were calculated with a short-lasting analysis of EKG recordings. Time domain-related, frequency domain-related, as well as non-linear analysis parameters, were compared between the two groups. Results: Compared to the R-TLE group, L-TLE subjects showed a statistically significant decrease in low frequency (LF) (p<0.01) and low frequency/high-frequency ratio (LF/HF) (p<0.001) as well as increased HF values (p<0.01), parameters indicative of the presence of an increased vagal tone. In a subgroup analysis that took into account the seizure types, responses to antiepileptic drugs, seizure frequencies, and etiology, the LF/HF ratio was significantly lower in all the L-TLE subjects. Conclusions: The main finding of the study is that, compared to R-TLE, L-TLE is associated with increased vagal tone. These results indicate that patients with TLE exhibit a lateralized cardiac autonomic control. L-TLE patients may have a lower risk of developing cardiac dysfunctions and less susceptible to develop SUDEP.